Is Design Attraction and Image Increasing Purchase Intention fermented beverage?: A case study on Gen Z in West Jakarta - Nusraningrum, Dewi; Bakhour, Alyssa Edwina Imad Khalid; Rizky, Dede; Ahrul Putra Mangku (Business and Entrepreneurial Review, 2024)
Due to their benefits, fermented beverages combined with fruits have become a trend among health-conscious consumers. However, the taste may not always meet consumer expectations, hence the need for packaging design that can attract consumers. This research aims to determine the influence of product design attraction and brand image provision on purchase intention toward the offered product design. The population size of the study is unknown; therefore, convenience sampling is used. The data obtained is processed using SEM-PLS. The results indicate that brand image plays an important role in increasing purchase intention, and attractiveness has a strong influence on brand image. However, attractiveness does not have a significant direct influence on purchase intention. This shows the importance of strengthening brand image to drive consumer purchase intention, while attractiveness can be used as a tool to improve brand image.